Theologie des Alten Testaments - Schmid, Konrad (Mohr Siebeck, 2019)
Theology of the Old Testament.
PublicationDate: 20190410
Keywords: Hermeneutik -- Bibel -- Kanon -- Hebräische Bibel -- Tora -- Studienliteratur -- Altes Testament -- Studienliteratur - Theologie -- Textbooks - Theology -- Array